Feeding habits of mudskipper fish (Priopthalmus argentiliniatus) in the mangrove ecosystem on The Northern Coast of Aceh - Dewiyanti Irma; Salsabilla Sarah (BIO Web of Conferences)
The mudskipper fish is one of the native fishes inhabit in mangrove ecosystem. Mangrove ecosystems are suitable habitats for marine life with high fauna diversity. Information about the feeding habits of mudskipper fish is essential to make domestication efforts for the conservation of mudskipper. Food determine the extent of distribution type and can control the size a population. This research was conducted in May until July 2024 in the mangrove ecosystem of Northern Aceh’s coast. The study aims to analyze the feeding habits of mudskippers in the mangrove ecosystem of Northern Aceh. Fish samples were collected using the purposive sampling method at four different locations. A total of 80 individuals were obtained, and their stomachs and intestines were preserved using a 4% formalin solution. The type of food was observed under a microscope in the Marine Biology Laboratory, Faculty of Marine and Fisheries, USK. The research identified 6 major food types, namely Phytoplankton, Nematodes, Crustaceans, Polychaeta, Hexapod, and litter fragments. The highest index of preponderance (IP) value showed that nematodes were the main food of mudskipper fish which have an IP value was 47%, some research found that nematode is one of foods that obtained in the mudskipper stomachs. The mudskipper fishes inhabit in mangrove ecosystem of the north Mangrove coast of Aceh are categorized as carnivorous fish.